2007
DOI: 10.1016/j.devcel.2007.04.012
|View full text |Cite|
|
Sign up to set email alerts
|

Sequence and Expression Differences Underlie Functional Specialization of Arabidopsis MicroRNAs miR159 and miR319

Abstract: Many microRNAs (miRNAs) are encoded by small gene families. In a third of all conserved Arabidopsis miRNA families, members vary at two or more nucleotide positions. We have focused on the related miR159 and miR319 families, which share sequence identity at 17 of 21 nucleotides, yet affect different developmental processes through distinct targets. MiR159 regulates MYB mRNAs, while miR319 predominantly acts on TCP mRNAs. In the case of miR319, MYB targeting plays at most a minor role because miR319 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
303
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(337 citation statements)
references
References 44 publications
31
303
0
3
Order By: Relevance
“…It has been previously shown that the miR159 and miR319 families are related in sequence and targets but that divergent expression and slight sequence variation allows for specific biological functions for these distinct miRNAs (Palatnik et al, 2007). After our sequence analysis of A. coerulea, it is not possible to determine conclusively if 2183893560 and 2185799162 encode miR159 and/or miR319.…”
Section: Mir159/319mentioning
confidence: 92%
See 1 more Smart Citation
“…It has been previously shown that the miR159 and miR319 families are related in sequence and targets but that divergent expression and slight sequence variation allows for specific biological functions for these distinct miRNAs (Palatnik et al, 2007). After our sequence analysis of A. coerulea, it is not possible to determine conclusively if 2183893560 and 2185799162 encode miR159 and/or miR319.…”
Section: Mir159/319mentioning
confidence: 92%
“…The fact that miR529 appears to be closely related to miR156 raises the possibility that it may have been lost without ill effect, possibility due to some redundancy with miR156. Before this hypothesis is tested, detailed work comparing miR156 and miR529 and their target specificity, similar to Palatnik et al (2007) where they determined that subtle sequence and expression differences in the related miR159 and miR319 families led to distinct functions, needs to be performed.…”
Section: Mir529mentioning
confidence: 99%
“…A possible mechanism could involve stimulation of DUO1 turnover via miR159-mediated regulation since the DUO1 transcript contains a functional miR159 binding site (Palatnik et al, 2007). Borges et al (2011) found that miR159a was significantly enriched in sperm cells and miR159-guided cleavage products as well as noncanonical products were detected in wild-type inflorescences and pollen Allen et al, 2010).…”
Section: Daz1 and Daz2 Are Required For Sperm Cell Differentiation Anmentioning
confidence: 99%
“…However, with the modified structure, the 21-paired-base rule would cause DCL1 to release a 21-nt miR173; in Fig. 2A, this modified construct is termed MIR173 21 , and the unmodified construct is termed MIR173 22 .…”
mentioning
confidence: 99%